Final Report : Facilitating Staff and Student Engagement with Graduate Attribute Development, Assessment and Standards in Business Faculties. - Taylor, Tracy; Thompson, Darrall; Clements, Lucille; Simpson, Lynette; Paltridge, Andrew; Fletcher, Marty; Freeman, Mark; Treleaven, Lesley; Lawson, Romy; Rohde, Fiona (Australian Learning and Teaching Council (ALTC), 2009)
Final report from a project that aimed to promote strategic change in advancing graduate attribute development in business education through staff and student engagement with learning and assessment processes that embed attribute development. This focus is of upmost importance as Australian business schools seek to obtain international accreditation, such as that of the Association to Advance Collegiate Schools of Business (AACSB) which requires each degree program specify learning goals and demonstrate a student's achievement of them. The participating institutions had all achieved initial AACSB accreditation and were involved in the maintenance of accreditation process. A social constructivist approach to graduate attributes was adopted, whereby assessment processes, criteria and standards were framed within an active engagement and participation of both students and educators, supplemented by using a pre-existing online assessment system. Outcomes included a perceived increase in student and staff awareness of graduate attributes. Self-assessment aided students in developing a better understanding of their attribute development, with the data suggesting they became more accurate in self-evaluation over subsequent assessment submissions. The project implementation facilitated the development of a community of practice between the four partner institutions which engaged in numerous productive discussions that heightened awareness and provided solutions around a range of issues.